Biodiversity and Ecosystem Status of Mangroves in the Belawan Estuary, North Sumatra Province, Indonesia - Ahmad Muhtadi; Rusdi Leidonald; Amanatul Fadhilah; Arya Yusuf Habibi; Natasya Rebekka Manalu; Decy M. Carolina Nasution; Parhan Pulungan; Salma Begum (Journal of Sylva Indonesiana, 2026)
Estuaries function as sediment deposition zones that provide essential substrates for mangrove development. Consequently, estuaries and mangroves constitute integral components of coastal ecosystems. The mangrove ecosystem in the Belawan Estuary, North Sumatra Province, is increasingly threatened by rapid urban expansion in Medan City. This study aimed to assess mangrove biodiversity, structural characteristics, and ecological status in the Belawan Estuary. Field surveys were conducted in November 2023 across 28 sampling stations representing seaward, middle, and landward sections of the estuary. Vegetation data were analyzed using density, diversity, evenness, dominance, and Importance Value Index (IVI). A total of 26 mangrove species were recorded, comprising 21 true mangrove species and 5 associated species. The most widely distributed species were Avicennia marina, Avicennia lanata, and Nypa fruticans. Mangrove density ranged from 533 to 2,733 ind ha⁻¹, with an average of 1,420 ind ha⁻¹. Shannon–Wiener diversity values ranged from 0.04 to 1.95, indicating relatively low diversity in several landward stations dominated by N. fruticans. Although the overall condition of mangroves in the Belawan Estuary is classified as good, the ecosystem remains highly vulnerable to land-use conversion under the revised spatial planning framework. Strengthening conservation-oriented spatial policy is therefore essential to ensure long-term ecosystem sustainability.